Improvement of Learning Quality at SDN Ngancar 1 Through the Use of Technology-Based Media in the Umsida Community Service Program : Peningkatan Kualitas Pembelajaran di SDN Ngancar 1 Melalui Penggunaan Media Berbasis Teknologi dalam Program KKN-P Umsida - Hayati, Anis Khoirin; Sari, Ervina Fatika; Nihayah, Durrotun; Sandy, Rizky Rahmahdian; Amelia, Ananda Firly (International Consortium of Education and Culture Research Studies, 2025)
Community service activities through the Muhammadiyah Sidoarjo University (UMSIDA) Real Work Lecture - Pencerahan (KKN-P) at SDN Ngancar 1 aim to improve the quality of learning by utilizing technology-based media such as ppt, animated videos, and electric boards as interactive media. The electric board is used as an evaluation tool that displays questions and answers, where students are asked to answer correctly so that the lights on the board can light up as an indicator of the correct answer. The methods used in this activity include observation, planning, implementation and evaluation. The evaluation results show that this innovation succeeded in creating a more interesting learning atmosphere, increasing student involvement in discussions, and strengthening understanding of the teaching material. However, the challenge faced is the limited number of technological devices available in schools. Apart from that, case-based learning methods and interactive quizzes are also applied to improve students' critical thinking. However, the challenge faced is the limited number of technological devices in schools. Therefore, further support is needed for the sustainability of this program so that it can continue to provide benefits for learning.